Surgical resection for hepatocellular carcinoma with portal vein tumor thrombus in the Asia-Pacific region beyond the Barcelona Clinic Liver Cancer treatment algorithms: a review and update - Ye, Jia-Zhou (Oncotarget, 2017)
Portal vein tumor thrombus (PVTT) usually worsens prognosis of hepatocellular carcinoma (HCC), as characterized by aggressive disease progression, impaired liver function and tolerance to treatment. Conventionally, the European Association for the Study of the Liver (EASL) and the American Association for the Study of Liver Diseases (AASLD) accepted the Barcelona Clinical Liver Cancer (BCLC) treatment algorithms, identifying PVTT as an absolute contra-indication of surgical resection for HCC. HCC-PVTT patients are offered sorafenib as the standard treatment. Evidently, SHARP and Asia-Pacific trials demonstrated that sorafenib only improves overall survival by approximately 3 months in patients with advanced HCC. Besides, BCLC treatment algorithm does not provide different therapeutic recommendations for different degree of PVTT, and only supports single treatment option for each stage of HCC rather than a combination of comprehensive treatments, which limited individual and best care for every HCC-PVTT patients. In the past few years, many surgeons do not restrict surgical resection to HCC with PVTT. There have been new reports demonstrated that surgical treatment is feasible for selected HCC-PVTT patients with resectable tumor and moderate liver function to prolong survival period and elevate life quality as long as PVTT limited to the first-order branch, whereas non-surgical treatments fail to provide comparable therapeutic effects. At present, guidelines on HCC management from mainland China, Japan, and Hong Kong have been updated and a consensus of Asia-Pacific experts has established that portal venous invasion is not an absolute contradiction of surgical resection for HCC. This review summarized the emerging data on surgical resection for HCC-PVTT patients beyond the BCLC treatment algorithms and discussed recent therapeutic conceptualchanges in the Asia-Pacific region.